The Effect of Nutritional Habits on Bone Minerals Density in Women with Postmenaposal Osteoporosis - Akarsu, Gökhan Doğukan; Şahan, Özlem; Akarsu, Rukiye Höbek; Yalman, Eylem (Progress in Nutrition, 2021)
Study Objectives: It was stated that the effect of dietary habits is of great importance in the prevention, pathogenesis, and treatment of osteoporosis. This descriptive and cross-sectional study was conducted to determine the effect of nutritional habits on bone mineral density in postmenopausal women with osteoporosis. Methods: The research was completed with 158 women who applied to the orthopedics and traumatology outpatient clinic with the diagnosis of postmenopausal osteoporosis between October 2020 and April 2021 in a practice and research hospital in Central Anatolia. The data were collected with the DEXA result reports in the patient files and the Patient Identification Form created by the researchers by scanning the literature. Results: 94.3% of the women included in the study smoked, 98.1% did not drink alcohol, 48.1% occasionally consumed coffee, 54.4% daily 3 cups of tea, 45.6% decently consumed cereals and cereal products, 39.3% sometimes consumed milk and dairy products. 82.3% of participants do not receive vitamin D and 88% do not receive calcium support therapy. Conclusion: It was determined that smoking, tea consumption, and BMI of women did not affect bone mineral density (p>0.05). It was determined that coffee consumption, frequently consumed food type, and taking vitamin D and calcium supplements affected bone mineral density (p<0.05).